Exploring the archetypes of engineer-to-order: an empirical analysis. Issue 3 (7th March 2016) - Willner, Olga; Powell, Daryl; Gerschberger, Markus; Schönsleben, Paul
Abstract : Purpose: – The purpose of this paper is to conceptualize archetypes of engineer-to-order (ETO) to support companies in determining the appropriate degree of design standardization and automation, and as a result achieve superior performance. Products of ETO manufacturers are classified in a 2×2 matrix using annual units sold and engineering complexity as dimensions. Design/methodology/approach: – This research adopted a theory refining approach based on multiple case studies. Seven ETO manufacturers from different industry sectors participated in the study. Data collection was primarily based on a series of in-depth interviews supported by observations and archival sources. Findings: – The paper proposes four distinct archetypes of ETO (complex, basic, repeatable, and non-competitive) and empirically validates three of them. The organizational structures and processes most suitable for the different archetypes are described, and standardization and automation strategies are linked to the quadrants of the matrix. The matrix can support practitioners in making strategic choices and provides a framework for benchmarking their ETO products and processes. Originality/value: – Existing conceptualizations of ETO consider the company as the primary object of investigation, rather than the product or product family. However, companies often have different product families demanding different strategies. Also, there is little or no focus on the engineering perspective. The authors move the engineering perspective to the center of investigation and identify a set of standardization and automation strategies for different types of ETO products.